Sistem Informasi Kinerja Layanan Laboratorium Medis dengan Metode Six Sigma - Dewi, Anindita Kusumastuti; Widiyanto, Ibnu (Universitas Diponegoro, 2015)
Medical Laboratory currently holds a very important role in medicine. Evaluation of laboratory quality plays a very important to maintain accurate laboratory results. This study aims to design an information system performance based on the same perception of medical laboratory services from customers using Six Sigma methods and frameworks using ServQual questionnaire. Selection of Six Sigma itself is based on this method can measure the extent to which each process deviates from its purpose as well as to reduce the variation of each of the attributes.Â Six Sigma DMAIC namely (Define, Measure, Analyze, Improve, Control) preferred because the end result will not yield new products, but only improvements on existing processes. The results of this calculation will be presented in the form of a dashboard for easier management in understanding the results of the evaluation. From the system can be obtained an average value of consumer perceptions terhdap performance today is 2,883, consumer expectations on the performance of 3.3768, the gap between the perceptions and expectations of consumers is -0.4936, customer satisfaction will be the performance of the current 85.37%, the value of 423 360 DPMO and sigma value there at the 2.07664 level.Â